2008
DOI: 10.5694/j.1326-5377.2008.tb01981.x
|View full text |Cite
|
Sign up to set email alerts
|

Incidence of bariatric surgery and postoperative outcomes: a population‐based analysis in Western Australia

Abstract: Objective: To investigate the incidence of bariatric surgery and postoperative outcomes in a population‐based cohort of patients in Western Australia over a 17‐year period. Design and setting: A population‐based incidence study of all bariatric procedures (n = 1403) performed in WA hospitals over the period 1988–2004, based on hospital morbidity and death data from the WA Data Linkage System. Main outcome measures: Changes in incidence of bariatric procedures over time; mortality and complications within 30 da… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
25
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(25 citation statements)
references
References 21 publications
0
25
0
Order By: Relevance
“…Bariatric surgery has matured into a distinct surgical discipline over the last two decades with an abundance of large population‐based studies demonstrating its safety and effectiveness as a treatment for obesity . Despite this, bariatric surgery has largely remained the domain of younger patients with most publications consistently reporting mean ages below 45 years . However, it is the older age groups with the greatest prevalence of obesity and obesity‐related comorbidities that stand to potentially benefit the most from effective weight loss treatments where there exists a reluctance in the uptake of bariatric surgery.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Bariatric surgery has matured into a distinct surgical discipline over the last two decades with an abundance of large population‐based studies demonstrating its safety and effectiveness as a treatment for obesity . Despite this, bariatric surgery has largely remained the domain of younger patients with most publications consistently reporting mean ages below 45 years . However, it is the older age groups with the greatest prevalence of obesity and obesity‐related comorbidities that stand to potentially benefit the most from effective weight loss treatments where there exists a reluctance in the uptake of bariatric surgery.…”
Section: Discussionmentioning
confidence: 99%
“…It brings together eight core data elements (birth records, midwives’ notifications, cancer registrations, inpatient hospital morbidity, inpatient and public outpatient mental health services data, death records, emergency department data collection and the Western Australian electoral roll). The accuracy of this database has been previously validated and formed the basis of several large, published population‐based studies . Prior approvals from our local institution and the Western Australian Department of Health Human Research Ethics Committee were granted before the release of de‐identified data in a format using 10th edition international classification of diseases (ICD‐10) diagnostic and procedure codes.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…However, despite being the only curative treatment for oesophageal/gastro-oesophageal cancer patients, oesophagectomy is associated with significant operative morbidity and mortality [5-7]. Key performance measures of oesophagectomy include 30-day mortality, hospital length-of-stay and post-surgery complication rate [8-17]. Factors influencing outcomes following oesophagectomy include hospital/surgeon factors (peer group/volume, surgical experience), tumour stage, histology and location, surgery type and patient comorbidity; with better outcomes reported in high volume hospitals, patients with non-metastatic disease (approximately 60% of patients), adenocarcinoma (the incidence of which is increasing), and when transhiatal oesophagectomy is performed [18-25].…”
Section: Introductionmentioning
confidence: 99%